Individualized surveillance of chronic hepatitis B patients according to hepatocellular carcinoma risk based on PAGE-B scores. Issue 12 (December 2021) - Kim, Ji Hyun; Kang, Seong Hee; Lee, Minjong; Choi, Hoon Sung; Jun, Baek Gyu; Kim, Tae Suk; Choi, Dae Hee; Suk, Ki Tae; Kim, Moon Young; Kim, Young Don; Cheon, Gab Jin; Baik, Soon Koo; et al.
Abstract : Background and aims: Current guidelines for chronic hepatitis B (CHB) patients are to undergo surveillance for hepatocellular carcinoma (HCC) with 6-month ultrasonography. We aimed to compare detection rates of very-early-stage HCC in two groups: group A, undergoing 6-month ultrasonography versus group B, undergoing 6-month ultrasonography alternating with dynamic computed tomography (CT). Methods: This retrospective study assessed 2151 CHB patients under entecavir/tenofovir therapy from 2007 to 2016. Detection rates of very-early-stage HCC were compared between groups A/B at intermediate/high risk based on platelets, age, gender-hepatitis B scores. The primary endpoint was the proportion of patients in each group with very-early-stage HCC. Cox proportional hazards model was used to assess the effect of surveillance modalities to detect very-early-stage HCC. Results: Five-year cumulative HCC incidence rates in group A were 15.0% not significantly different from 18.2% in group B at high risk ( P = 0.17). Detection rates of very-early-stage HCC were significantly higher in group B than in group A ( P < 0.001), and surveillance using CT alternating with ultrasonography was significantly associated with detection of very-early-stage HCC (hazard ratio 3.89, P < 0.001). Among intermediate-risk patients, difference between detection rates of very-early-stage HCC in groups A and B was not significant (P = 0.30), and surveillance using CT alternating with ultrasonography was not significantly associated with detection of very-early-stage HCC (hazard ratio 1.61, P = 0.23). Conclusion: In high-risk CHB patients, surveillance using CT alternating with ultrasonography led to higher detection rates of very-early-stage HCC compared to surveillance using ultrasonography. Abstract : Supplemental Digital Content is available in the text.